2018
DOI: 10.30635/2415-0142.2015.01.3
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Trivalent Chromium in the Aquatic Macrophytes Typha domingensis L. and Pontederia parviflora Alexander

Abstract: The phytoremediation employs the use of plants and is rapidly gaining interest due to effective and inexpensive cleanup of wastewater contaminated with metals, hydrocarbons, pesticides and chlorinated solvents. This study compares the performance of the Typha domingensis and Pontederia parviflora under similar conditions, in the absorption of trivalent chrome. The determination of the absorption capacity of the species was set in four tests of survival. The aquatic macrophytes were maintained in solution of 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The chromium was slightly transported from the root to the stem in high concentrations, totally different behavior observed in the low concentrations, previous studies also showed this tendency of metal accumulation in stem (Balassa et al, 2010;Souza et al, 2015), in that experiment P. parviflora showed ability to absorb 99% of the chromium of solutions in 48 hours. A study with Lemna minor showed an absorption capacity of 10% in 120 hours (Thayaparan et al, 2015), and the authors considered the species to be a hyperaccumulator to the bioconcentration factor.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The chromium was slightly transported from the root to the stem in high concentrations, totally different behavior observed in the low concentrations, previous studies also showed this tendency of metal accumulation in stem (Balassa et al, 2010;Souza et al, 2015), in that experiment P. parviflora showed ability to absorb 99% of the chromium of solutions in 48 hours. A study with Lemna minor showed an absorption capacity of 10% in 120 hours (Thayaparan et al, 2015), and the authors considered the species to be a hyperaccumulator to the bioconcentration factor.…”
Section: Discussionmentioning
confidence: 65%
“…In the environmental area, one of the major applications of phytochelatins determination is the selection of species capable of hyperaccumulating metals for use in the phytoremediation process, which enables the decontamination of environments by the sorption of metals by plants (Hernández et al, 2015). Studies with Pontederia parviflora Alexander in the absorption of metals have been developed and this species has proved to be resistant to heave metals (Balassa, Souza, & Lima, 2010) and in different environmental conditions (Souza, Locastro, Lima, & Iwakura, 2015).…”
Section: Introductionmentioning
confidence: 99%